Genogroup II Noroviruses Efficiently Bind to Heparan Sulfate Proteoglycan Associated with the Cellular Membrane - Tamura, Masaru (American Society for Microbiology, 2004)
Norovirus (NV), a member of the family Caliciviridae, is one of the important causative agents of acute gastroenteritis. In the present study, we found that virus-like particles (VLPs) derived from genogroup II (GII) NV were bound to cell surface heparan sulfate proteoglycan. Interestingly, the VLPs derived from GII were more than ten times likelier to bind to cells than were those derived from genogroup I (GI). Heparin, a sulfated glycosaminoglycan, and suramin, a highly sulfated derivative of urea, efficiently blocked VLP binding to mammalian cell surfaces. The reagents known to bind to cell surface heparan sulfate, as well as the enzymes that specifically digest heparan sulfate, markedly reduced VLP binding to the cells. Treatment of the cells with chlorate revealed that sulfation of heparan sulfate plays an important role in the NV-heparan sulfate interaction. The binding efficiency of NV to undifferentiated Caco-2 (U-Caco-2) cells differed largely between GI NV and GII NV, whereas the efficiency of binding to differentiated Caco-2 (D-Caco-2) cells did not differ significantly between the two genogroups, although slight differences between strains were observed. Digestion with heparinase I resulted in a reduction of up to 90% in U-Caco-2 cells and a reduction of up to only 50% in D-Caco-2 cells, indicating that heparan sulfate is the major binding molecule for U-Caco-2 cells, while it contributed to only half of the binding in the case of D-Caco-2 cells. The other half of those VLPs was likely to be associated with H-type blood antigen, suggesting that GII NV has two separate binding sites. The present study is the first to address the possible role of cell surface glycosaminoglycans in the binding of recombinant VLPs of NV.